Pengaruh Metode Struktural Analitik Sintetik Terhadap Keterampilan Menulis Permulaan dan Hasil Belajar Kelas 1 Sekolah Dasar - Ektansa Masyaul Afla; Diah Sunarsih; Budi Adjar Pranoto (Peneliti.net, 2022)
Based on the results of initial observations and interviews consisting of 9 male students and 9 female students from 18 students there were 6 students who were able to write letters, words, and sentences well, although they were still in the early stages. 3 students who cannot write letters, and 9 students who cannot write simple words with several letters. The method used in this study uses a quantitative method of correlation of sampling techniques with saturated samples. Data collection techniques for synthetic analytical structural learning used observation sheets, for writing skills using a short description test, and for learning outcomes for theme 5 sub-theme 4 learning 1 using multiple choice tests. Analysis of the research data using the t test. The results obtained are (1) the SAS method on writing skills from the t-test obtained a significance value of 0.018, which means 2.639 > 2.13145. This shows that Ha1 and Ho1 are accepted, which means that there is an effect of X with Y1. (2) the SAS method on learning outcomes for theme 5 subtheme 4 learning 1 obtained a significance value of 0.009. From the results of these calculations, it can be seen that 2.967 > 2.13145, or tcount > ttable and 0.09 > 0.05 or the significance value > 0.05. It can be seen that Ha2 and Ho2 are accepted, which means that there is an influence of synthetic analytic structural methods and writing skills.